Towards Community-Directed Climate Adaptation Research (C-DAR) - Bowness, Evan; Nehemy, Magali; Tremembé, Mateus; Martins, Davi Timóteo (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
The disconnection between humans and their surrounding ecologies, intensified since the industrial revolution and often described as the “metabolic rift,” has profoundly influenced dominant research practices as enterprises of knowledge production. As such, much research today, including climate change research, is disconnected from the land and the communities who depend on and steward it. This paper starts by briefly tracing a response to this disconnection, the emergence of community-engaged approaches to action research. Turning on the urgency of community adaptation under the climate emergency, we point to how this trajectory has seeded a paradigm shift to what we are referring to as community-directed research (C-DAR). Drawing on dialogues with three Indigenous community partners in Brazil—the Tremembé, Mundurukú, and Guaraní—we theorize how C-DAR could navigate four critical boundaries to bridge the rift between researchers and the land: The rift between western science and Indigenous and local knowledges; the rift between natural and social sciences; the rift between institutional (university) and community contexts; and the rift between the Global South and the Global North. We conclude with an observation that the acronym “C-DAR” is phonetically identical in Brazil to the Portuguese reflexive verb “se dar” which can mean “to give oneself to something.” In this spirit of “se dar,” we offer our paper as a call for experiments in reparative approaches to research, inviting scholars to reflect on their willingness to engage with this ethos.